2020
DOI: 10.34190/jel.18.5.005
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Integration of E‑Learning by Preservice Science Teachers: Structural Model Development and Testing

Abstract: This study investigated the possible factors that predict e‑learning integration into the teaching and learning of science subjects among preservice science teachers. A unified e‑learning integration model was developed in which factors such as attitude, intention, skill and flow experience served as precursors of e‑learning integration. This was done to help close the gap that no previous studies have developed a structural model to statistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…These results contrast with those obtained by Baydas and Goktas [53], Teo and Milutinovic [54] and Sánchez-Mena et al [55], since their studies found no significant differences by gender in regard to intention to use. It should not be forgotten that the intention to use ICT leads to its integration into teaching and research work, according to data obtained by Olugbara and Letseka [52], Anderson and Maninger [50], and Venkatesh et al [51]. In this study, it was found that the level of integration for both genders was medium-high, although slightly higher in males (age range of less than 40 years) in relation to the use of data analysis programs, bibliographic managers and the use of social networks to disseminate publications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results contrast with those obtained by Baydas and Goktas [53], Teo and Milutinovic [54] and Sánchez-Mena et al [55], since their studies found no significant differences by gender in regard to intention to use. It should not be forgotten that the intention to use ICT leads to its integration into teaching and research work, according to data obtained by Olugbara and Letseka [52], Anderson and Maninger [50], and Venkatesh et al [51]. In this study, it was found that the level of integration for both genders was medium-high, although slightly higher in males (age range of less than 40 years) in relation to the use of data analysis programs, bibliographic managers and the use of social networks to disseminate publications.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the quality of the ICT resources that researchers have can condition their integration [62], as can be seen in the influence exerted by the fifth dimension (D5-quality). Finally, it can be highlighted that the greater the intention to use ICT, the greater the probability of integration [52], in this sense the sixth dimension (D6-intention) (Intention to use) also exerts a notable influence. For all these reasons, it can be said that the proposed model is a robust model.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…While the Covid-19 pandemic has put enormous pressure on South African higher education institutions (that is, adapting to remote and digital learning), it has also fast-tracked the adaptation necessary to align to 21 st -century needs. Calling for quick adaptation on the part of educational systems, the catalytic impact of Covid-19 can thus be viewed as beneficial to South Africa's educational landscape in the long run, especially considering the growing pressure to digitalise learning (Olugbara & Letseka, 2020). Given that the virus had a ripple effect from starting point(s) that spread to the global scale, higher education has had to embrace this reality, and further accept that the legacy of the Covid-19 crisis will be with us for years (perhaps even decades) to come.…”
Section: Woldegiorgismentioning
confidence: 99%
“…Thus, Content and Language Integrated Learning (CLIL) when used systematically, contributes to a significant increase in motivation as the main mechanism for activating the process of teaching foreign languages to school students, since their attention is involuntarily held on interesting, new and meaningful language material [Olugbara & Letseka, 2020]. The professionallyoriented subject of the classes meets the cognitive needs of students and leads to the active assimilation of new knowledge [Erusalimov et al, 2021].…”
Section: Discussionmentioning
confidence: 99%